PM di Pekanbaru Tahun 2024: Sumber dan Transportasi Atmosfer Menggunakan Trajektori Mundur HYSPLIT - Mustaqiman, Aulia Nur; Shirajjudin , Angga Dheta (Department of Environmental engineering, Faculty of Science and Technology, Islamic State University Sunan Ampel Surabaya, 2025)
This study investigates the concentration and dispersion patterns of PM in Pekanbaru, Indonesia, from January to November 2024, using a combination of air quality data and HYSPLIT trajectory modeling. The analysis identifies the peak PM concentration on September 22–23, 2024, reaching 55.74 µg/m³, which corresponds to an Air Quality Index (AQI) value of 131—classified as